Fire and ice [videorecording (DVD)] - Bakshi, Ralph; Thomas, Roy, 1940-; Conway, Gerry (Blue Underground, Inc., 2008)
In this animated tale, muscular Larn rescues damsel Teegra from sorcerer Lord Nelkron. Animated by Ralph Bakshi and Frank Frazetta.